Reconstruction of Lower Extremity with Perforator Free Flaps by Free Style Approach in Pediatric Patients - Song, Jin Woo; Ben-Nakhi, Muneera; Hong, Joon Pio (Journal of Reconstructive Microsurgery, 2012)
Pediatric reconstruction using microsurgery is accepted normal practice, and the use of perforator flaps is slowly increasing. This study presents clinical work using various perforator free flaps by free style approach to reconstruct lower extremity soft tissue defects in pediatric patients and evaluates its efficacy. Between June 2002 and February 2011, 32 cases (mean age: 10.1 years) were reconstructed with free style perforator free flaps. Retrospective evaluations for flap survival, growth character, and other associated morbidities were performed. Flaps used in this series are anterolateral thigh (ALT) perforator, superficial circumflex iliac artery perforator (SCIP), upper medial thigh perforator, and posterior interosseous perforator free flaps. The free style approach for pedicle dissection was successful in all cases. Early postoperative complications were 15.6% from hematoma collection to partial loss of flap. Although there was no total loss in this series, one case needed additional flap coverage to cover the partial loss of the flap. The long-term follow-up showed contracture along the margin, with 16% needing a releasing procedure. Bone growth was not affected by flap contracture. The overall results show perforator flaps using the free style approach to be a reliable and feasible approach for lower extremity reconstruction in the pediatric population.
Keywords: pediatric reconstruction; free style reconstruction; perforator flaps